2017
DOI: 10.20959/wjpps20174-8872
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Prediabetes and Associated Risk Factors Among Adults in Yaounde –Cameroon

Abstract: Bivariate relationships between prediabetes and sex, obesity, age, hypertension was etablished and multivariate logistic regression analyses were used to identified pre-diabetes risk factors. Results: The overall prevalence of prediabetes was (15.03%) higher in women than in men. Through multivariate logistic, it appeared that female sex, overweight/obesity were the risk factors for prediabetes development. Conclusion: The prevalence of prediabetes was high in the studied population of Yaounde. Female sex, ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, considering the high prevalence of CVRF in this population, the inappropriate diet, and the prevalence of infectious conditions, this prevalence seems to be reliable [37]. Furthermore, Kamdem et al reported increased overweight/obesity and impaired fasting blood glucose in teenagers, the same as Mandob who reported a prediabetes prevalence of 15.3% [50,51]. It is therefore conceivable that such a population put in this environment could develop diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…However, considering the high prevalence of CVRF in this population, the inappropriate diet, and the prevalence of infectious conditions, this prevalence seems to be reliable [37]. Furthermore, Kamdem et al reported increased overweight/obesity and impaired fasting blood glucose in teenagers, the same as Mandob who reported a prediabetes prevalence of 15.3% [50,51]. It is therefore conceivable that such a population put in this environment could develop diabetes.…”
Section: Discussionmentioning
confidence: 95%